m6A-Mediated Upregulation of LINC00857 Promotes Pancreatic Cancer Tumorigenesis by Regulating the miR-150-5p/E2F3 Axis - Meng, Xiangrui; Deng, Yanyao; He, Shuhan; Niu, Li; Zhu, Hongwei (Frontiers in Oncology, 2021)
The mortality and morbidity rates of pancreatic cancer (PC) have been increasing over the past two decades. Recent evidence indicates that long noncoding RNAs (lncRNAs) are usually dysregulated in the tumorigenesis and progression of PC. In the present study, we showed that the expression of LINC00857 was upregulated in PC and associated with poor prognosis based on the GEPIA database and validated in our PC tissues and cell lines. N6-methyladenosine (m6A) was highly enriched within LINC00857 and enhanced its RNA stability. Knockdown of LINC00857 remarkably inhibited the proliferation and promoted the apoptosis of PC cells. Then, by using bioinformation analysis and verified experiments, we identified that LINC00857 functioned as a competing endogenous RNA (ceRNA) for sponging miR-150-5p, leading to the upregulation of its target E2F3 in PC cells. Taken above, our study revealed a potential ceRNA regulatory pathway in which LINC00857 modulates E2F3 expression by binding to miR-150-5p, ultimately promoting tumorigenesis in PC. LINC00857/miR-150-5p/E2F3 regulatory axis may be taken as an alternative therapeutic target for treating PC.